Blind-Tie Remplissage: Technique and Sequence - Weston B. Gentry, M.D.; Larry D. Field, M.D. (Arthroscopy Techniques)
Patients with recurrent anterior shoulder instability and an associated Hill-Sachs lesion are commonly encountered by orthopaedic surgeons. Effective management of the Hill-Sachs lesion can be performed using an arthroscopic remplissage technique to fill the bony defect with the infraspinatus and posterior capsule. Various surgical techniques, anchor configurations, and tying mechanisms can be used to accomplish the remplissage procedure. The goal of this Technical Note is to describe our technique and sequence for accomplishing an arthroscopic “blind-tie” remplissage procedure. In this remplissage technique, the suture anchor sutures placed into the Hill-Sachs defect are tied in a blind fashion over the infraspinatus fascia without direct visualization from within the subacromial space.